Dve desetletji dinamike podjetniškega razvoja: GEM Slovenija 2022 (University of Maribor Press, 2023)
Two decades of dynamic entrepreneurial development: GEM Slovenia 2022. The GEM survey offers an in-depth analysis of the various social, cultural, political, and economic factors that impact the entrepreneurial landscape and activities, serving as a comprehensive framework for understanding national and entrepreneurial conditions. These factors play a crucial role in shaping individuals’ entrepreneurial decisions and the success of starting and operating businesses. Survey delivers unparalleled insights into a nation’s entrepreneurial characteristics, surpassing the information available from traditional statistical sources. The study also explores individuals’ and societies’ attitudes towards entrepreneurship, alongside the aspirations and qualifications of people at different entrepreneurial stages. By examining these aspects across countries, GEM identifies key drivers and obstacles for entrepreneurship, enabling stakeholders to cultivate a supportive entrepreneurial ecosystem. The latest GEM report is particularly noteworthy as it features a retrospective of the past two decades. Within this period, Slovenian entrepreneurship experienced significant changes, ranging from innovation promotion and startup development to economic crisis-related challenges.